2008
DOI: 10.1177/104063870802000304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Nested Polymerase Chain Reaction Assay to Differentiate Between Two Genotypes of Porcine Circovirus-2

Abstract: Porcine circovirus-2 (PCV-2) is associated with several diseases in pigs, including postweaning multisystemic wasting syndrome (PMWS). A new genotype of PCV-2 was isolated from swine farms with and without clinical PMWS in North America. The new genotype was differentiated in a separate cluster by phylogenetic analyses and is now named PCV-2b compared with PCV-2a for the previously known genotype. The purpose of this study was to develop and evaluate a nested polymerase chain reaction (nPCR) assay to detect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Generally, the nucleotide sequencing has been used to detect PCV2a and PCV2b [12], other approaches included PCR [16], nested PCR [17], PCR-RFLP [18] and TaqMan-based assay [27]. However, these methods were usually time consuming and high technical requirement, and were difficult to popularize in veterinary clinic practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the nucleotide sequencing has been used to detect PCV2a and PCV2b [12], other approaches included PCR [16], nested PCR [17], PCR-RFLP [18] and TaqMan-based assay [27]. However, these methods were usually time consuming and high technical requirement, and were difficult to popularize in veterinary clinic practice.…”
Section: Discussionmentioning
confidence: 99%
“…These controversial PCV2 new genotypes need further investigation. At present, PCR [16], nested PCR [17], PCR-RFLP [18], TaqMan-based assay [19], nucleotide sequencing and phylogenetic analysis [12] have been used to detect and differentiate PCV2a and PCV2b. However, the application of these methods is limited somewhat by the expensive PCR equipment, the long detection period or the high technical requirements [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The PCV2c genotype has only been found in Denmark to date [31]. In recent years, several reports have suggested that PCV2b is the predominant genotype in many countries worldwide, including Brazil [8,11], Canada [14,15], China [17,21,38], Cuba [29], Denmark [12], Germany [30], Japan [32], Korea [1,2,19,20], Slovakia [37], Spain [10], Sweden [33], Switzerland [39], Thailand [18] and the U.S.A. [6,23]. PCV2b might be more pathogenic than PCV2a [16,32].…”
mentioning
confidence: 99%
“…Recently, there are several excellent methods that can be used to identify the PCV2a and PCV2b; these include polymerase chain reaction (PCR) assay, nested PCR, real-time PCR and restriction fragment length polymorphism (RFLP) [5,14,15,16]. These methods are convenient and allow the testing of large number of clinical samples.…”
Section: Introductionmentioning
confidence: 99%